Experiments on the cultivation of dandelion for salad use: II The nutritive value and intrinsic quality of dandelion leaves - Kuusi, Taina; Hårdh, Kirsti; Kanon, Helena (Agricultural and Food Science, 1984)
In an extensive investigation concerning the utilization of dandelion, the feasibility of cultivating the dandelion for salad use has been studied. Properties making up the intrinsic quality, viz., nutritive value and content of nitrates, have been used as one criterion of suitability. The study material consisted of 11 Finnish agamospecies selected for their mild taste, and two middle-European cultivars, ’Vollherziger verbesserter’ and ’Vert de Montmagny’. The effects of cultivation methods were also studied: two levels of fertilization, and covering with black polyethelene film, black fibre cloth and bark humus layers of various thicknesses were compared. As criteria of the nutritive value, dry matter, soluble solids, mineral contents, in particular Ca, Mg, Fe and Mn, and vitamin C, were measured. The nitrate content as a criterion of intrinsic quality was also studied. In spring, the dry matter of the rosettes averaged 12.3%, in late summer 17.1 %. In spring the average content of soluble solids was 5.5 %, the mineral content 1.6 %. The amounts of the individually analyzed minerals Ca, Mg, Fe and Mn deviated somewhat from values in the literature, probably due to the methods of cultivation. The amount of vitamin C in spring was on average 42 mg/100g, varying between 29 and 53 mg/100g. The nitrate content was low: at highest 660 mg NO3/kg fresh weight. The influence of fertilizing level was slight. Even the levels of minerals and nitrates were not increased at the higher level of fertilization. Coverings had clear-cut effects. Where the covering effectively eliminated light, i.e. when black film, black fibre cloth or thick bark humus layer was used, the dry matter, soluble solids, mineral content and vitamin C values were decreased and the nitrate values increased. Compared with other plants used as salad greens, the nutritive value and particularly the amount of vitamin C in dandelion are much higher, although the values are considerably decreased if the leaves are bleached. If the mild tasting types studied here were cultivated, bleaching would not be necessary. The nitrate content in dandelion is generally low as compared with many other plants used as salad greens.